Biological activity of silver nanoparticles synthesized from untapped secondary metabolites of Olea europea endophytic Bacillus amyloliquefaciens - Fawad Hayat; Sumera Afzal Khan; Muddasir Khan; Zahoor Khan; Ho-Youn Kim; Abdul Qadeer; Khalid J. Alzahrani; Fuad M. Alzahrani; Muhammad Hamayun (PLoS ONE, 2025)
Endophytic microbes offer frequent contributions to the identification of novel biologically active compounds. The current study aimed to isolate untapped Olea europaea-associated Bacillus amyloliquefaciens and to explore their bioactive secondary metabolites as well as its mediated silver nanoparticles (AgNPs). B. amyloliquefaciens analysis revealed the existence of 23 compounds in metabolite extract by using Gas chromatography-mass spectrometry (GC-MS) analysis. AgNPs were synthesized by using metabolite extract and confirmed by using UV-Vis spectrophotometry, Energy Dispersive Spectroscopy (EDS), and Fourier Transform Infrared Spectroscopy (FTIR). B. amyloliquefaciens metabolite extract displays a high inhibition zone (19 mm) against Morganella morganii and Escherichia coli, while AgNPs exhibit high inhibition zone (22 mm) against M. morganii. The extract shows 64.8% and AgNPs display 99.8% antioxidant activity in 5mg/mL concentration. In analgesic effect, after 90 minutes at 100 mg/mL concentration, the extract shows a mean latency time of 17 seconds while AgNPs show 19 seconds, respectively. In conclusion, B. amyloliquefaciens metabolite extract and AgNPs exhibited significant antibacterial, antioxidant, and analgesic activities in various concentrations while comparatively AgNPs displayed higher bioactive potential. Endophytic bacteria associated with O. europaea have diverse bioactive metabolites with promising pharmaceutical activities, as well as their mediated AgNPs increase these activities. Further research on the exploration of endophytic bacterial metabolites and its mediated nanoparticles will prompt the discovery of novel bioactive compounds.